Finite element modeling of clinching process for joining dissimilar materials - Eshteyah, Mohanna; Hrairi, Meftah; Shaik Dawood, Mohd. Sultan Ibrahim; Mohiuddin, A. K. M. (Trans Tech Publications, Switzerland, 2015)
Clinching is one of the important new joining techniques, in which two plate metal parts are locally plastically deformed by mechanical interlock. Clinching is a mechanical joining method by using simple tools that consist of a punch, a die, and a blank-holder. The shapes of these tools are the most important parameters that control the final geometry of the clinch joints which in turn strongly affect the strength and quality of the final joint. In this study, finite element simulations are carried out to investigate some of the difficulties regarding the optimization of the process parameters, and major expected geometric parameters that will influence the strength, joinability, and the quality of the joint.